Nephrectomy associated with right renomegaly in a dog affected by hydronephrosis - Wajczyk, Talita; Rodrigo Von Muhlen, Rodrigo; Lustosa de Mello, Janaína; Furtado de Carvalho, Tatiane; de Abreu Pereira, Juliana; Teixeira, Leonardo; Effting, Ana Clara; Cristina Nehls Coutinho, Daina; Aparecida Ferreira, Ariele; Timboni Teixeira, William (Pubvet, 2020)
Hydronephrosis results from a total or partial obstruction of the lower urinary Hydronephrosis results from total or partial obstruction of the lower urinary tract, which promotes progressive dilation of the renal pelvis, and consequently, compression and atrophy of the parenchyma. Although its casuistry is low, its diagnosis is favored by clinical, laboratory and imaging exams. The aim of this study was to report the case of an adult mixed breed (SRD) dog with severe hydronephrosis that culminated in unilateral right nephrectomy. The animal had a distended abdomen with no painful response and a flank wound through which it drained blood and purulent secretion. Laboratory tests indicated normochromic normocytic anemia, leukocytosis with deviation to the left and increased plasma proteins. During the surgery, the right kidney was attached to the peritoneum, spleen, pancreas, omentum, liver and stomach. There were no free abdominal fluids or signs of peritoneal and / or retroperitoneal inflammation. Loss of renal parenchyma with replacement by intense fibrous connective tissue was verified microscopically. This report describes the evolution of this case from its initial consultation to the ninety days after the postoperative period. The underlying cause of the disease has not been clarified.